Efficient Streaming of Video Frames over Heterogeneous Wireless Network - Lavanya, K; R.Kanthavel, Dr; R.Dhaya, Dr (International Journal of Engineering and Technology, 2018)
Transferring high quality video stream through a heterogeneous wireless network has many challenges due to the varying data rate and round trip time(RTT) involved in the network and the more stringent quality of service(QoS) requirements of the multimedia application such as on time delivery , minimum delay etc. User datagram protocol (UDP), a connectionless, unreliable transport protocol has been widely used for transferring video frames.UDP cannot guarantee reliable information delivery andÂ  may lead to packet loss. The packet loss, increases with time varying bandwidth availability in the heterogeneous wireless networks. Transmission control protocol(TCP) can be an alternate transport layer protocol to provide reliable delivery of video information. But, using TCP for wireless networks has limitations due to misinterpretation of packet loss, frequent link failure, asymmetric link behaviour etc.,. which minimizes the throughput and in turn degrades the quality of the video frames transmitted. This paper analyses an efficient scheme to use Heterogeneous Environment Retransmission algorithm with SCTP (HERTS) to transfer video data in the heterogeneous environment. By using multi-homing and multi-streaming feature of Stream control transmission protocol (SCTP), the packet delivery rate, through put and delay requirements can be optimized. The transport layer model suggested in this paper aims at reducing the occupancy of the retransmitted packets in the link, by using a separate end to end path allotted for retransmission.Â Â